Associations between physical activity parenting practices and adolescent girls’ self-9 perceptions and physical activity intentions - Sebire, Simon; Haase, Anne M.; Montgomery, Alan A.; McNeil, Jade; Jago, Russell (Human Kinetics, 2014)
Background: The present study investigated cross-sectional associations between maternal and paternal logistic and modelling physical activity support and the self-efficacy, self-esteem and physical activity intentions of 11-12 year old girls. Method: 210 girls reported perceptions of maternal and paternal logistic and modelling support and their self-efficacy, self-esteem and intention to be physically active. Data were analysed using multivariable regression models. Results: Maternal logistic support was positively associated with participants’ self-esteem, physical activity self-efficacy and intention to be active. Maternal modelling was positively associated with self-efficacy. Paternal modelling was positively associated with self-esteem and self-efficacy but there was no evidence that paternal logistic support was associated with the psychosocial variables. Conclusions: Activity-related parenting practices were associated with psychosocial correlates of physical activity among adolescent girls. Logistic support from mothers, rather than modelling support or paternal support may be a particularly important target when designing interventions aimed at preventing the age-related decline in physical activity among girls.